ANALYSIS OF SERVICE QUALITY DESIGN WITH INTEGRATION OF KANO MODEL AND HOUSE OF QUALITY (HoQ) - Kusumastuti, Satya Adrianina; Kusmantini, Titik; Sabihaini, Sabihaini (Pattimura Proceeding, 2023)
Introduction/Main objectives: Determine the superior service quality provided by Matahari Department Store and what attributes can satisfy customers. Background problems: Quality service is something that can distinguish one retail store from another. Consumers will compare the service received with what is expected. The quality of this service will then look good or not from the consumer's perception of the entire service process received, not the basis of the perception of the service provider. Novelty: Research about service quality using the integration of Kano Model and House of Quality in retail industry is limited. Research methods: It used integration of Kano Model and House of Quality (HoQ) with PT Matahari Department Store as the object and customer as informants. Service quality attributes are taken from Servqual. Data gathered using observation, interview, and questionnaire. Finding/Results: (1) provide input to PT. Matahari Department Store regarding strategies that can improve service quality, by identifying and prioritizing service attributes that can meet customer needs using the Servqual method and the integration of the Kano Model with the House of Quality, (2) provide input on attributes that can be developed to improve customer satisfaction. Conclusion: (1) from the identification of service quality attributes using servqual, 1 attribute with a gap score of 0 is obtained and 16 attributes have a negative score, (2) from the combined results of Servqual with Kano Model classification, 12 attributes are obtained with category O (One Dimensional) which can improve the quality of service to customers and 5 attributes with category M (Must Be), (3) from the results of the integration of Servqual and the Kano Model which is included in the House of Quality, there are 6 technical responses above an average of 6% which can be used to meet customer expectations for service quality, so that they can satisfying customers